Development And Validation of Stability Indicating Rp- Hplc Method for Simultaneuos Estimation of Cephalexin and Clavulanic Acid - Maru, Khushbu; Ram, Darshit; Buddhadev, Sheetal (Journal of Neonatal Surgery, 2025)
The combined dosage form of cephalexin and clavulanic acid was tested using a stability- indicating RP-HPLC technique. The combined dosage form of cephalexin and clavulanic acid was tested using a stability-indicating rp-hplc technique.The measurement wavelength was found to be 228 nm. Linearity, accuracy, precision, robustness, LOD, and LOQ have all been verified for the approach. The concentration ranges of 62.5–187.5 μg/ml for clavulanic acid and 37.5–112.5 μg/ml for cephalexin were found to be linear. Using sodium dihydrogen phosphate monohydrate buffer (pH:5.0 with OPA): methanol in a 65:35% v/v ratio as the mobile phase, the rp-hplc approach showed better separation and asymmetry on an Intersil OCD C18 (250 x 4 mm, 4 μm) packed column at a flow rate of 1 ml/min. It was discovered that the retention times for cephalexin and clavulanic acid were 4.216 and 2.189 minutes, respectively. Drug products were subjected to oxidation, photolytic, thermal, acid, and base degradation during a stability study using forced degradation. Under the specified stress conditions, cephalexin and clavulanic acid were shown to degrade by 7–10%. The devised method, which can be employed for simultaneous estimation of cephalexin and clavulanic acid in their tablet dose form, was straightforward, precise, and specific